Identification pests and diseases of coffee plant on Mount Puntang as a basis for integrated pest management to support sustainable development goals - Luthfia, Ihda Siti; Ibrahim, Yusuf; Rahmat, Adi (Jurnal Mangifera Edu, 2024)
One of the main advantages in plantation exports in Indonesia is coffee plants, but it should be known that there are many types of pests associated with coffee planting. identifying pests and diseases is the basis for reducing possible crop losses. This research aims to control the growth of pest populations. This research uses a descriptive approach by directly following up in the field by making direct observations in sampling the data to be obtained. Performed by identifying the types of pests and diseases found in coffee plants in Gunung Puntang Bandung by making Belt Transect and performing 2 sampling techniques: hand sorting and beating tray. The overall pest species that were sampled in 3 sampling times in the Gunung Puntang Bandung coffee plantation consisted of 6 orders, and 27 pest species that attacked coffee plants. There are 5 types of damage caused by pests found in Gunung Puntang Coffee Plantation, namely leaf miner perforated leaves by Spodoptera litura and chrysomelidae, fruit rot and Green Coffee Scale Disease. There are five diseases identified, namely Cercospora leaf spot rust, Powdery mildew, Antarnoxa, and Coffee Berry Desease. The thing that affects the number of pests and diseases in Gunung Puntang coffee plantations is the climate and environmental conditions that are adequate for these pests to develop and grow.